Ethnographie historique de la zawiya Uqari à Guenzet (Kabylie) - Titem Bessah (L’Année du Maghreb)
Like many regions of the Maghreb, Kabylia is an area where one can observe a remarkable presence of places with religious purposes, locally referred to by the two terms: timɛemert (full place) and zāwiya (angle, corner). These Quranic educational institutions are often named after the saint founder. The establishment of saints in Kabylia seems to have occurred in two waves. The first wave dates back to the 12th-13th centuries, while the second, more significant, took place during the 16th-17th centuries. The installation of saints was then followed by the construction of religious establishments. This is the case of the zawiya founded by the saint Sidi Mohamed Uqari in the second half of the 17th century in Guenzet, a mountainous rural area located in the western part of the Guergour massif, between the cities of Sétif, Bordj Bou Arreridj, and Bejaia, a territory commonly identified with the At Yaala tribe.This article is a historical ethnography of this religious institution, analyzing its post-independence changes in connection with contemporary religious and political dynamics, and in light of the issues of the past. It first shows how reformism concretely influences the “traditional”/local representations and practices of sainthood. Then, it looks at how the state articulates such a religious institution with the official cult and tends to frame Algerian Islam following the rise of political Islam through the reorientation of religious education.Our analysis is based on data from an ethnographic survey conducted between July 2022 and August 2023. Our fieldwork approach combines direct observation of the sites and interviews (about ten) with the heads, sheikhs, and ṭulbā (or tulba: students/literate people) of the institution. Moreover, our respondents provided us with several manuscripts, old photographs, and other documents concerning the zawiya (internal regulations, various versions of the teaching programs, and administrative documents). This fieldwork is associated with a theoretical approach inspired by the dynamic perspective, which allows us to observe changes, both endogenous (within the zawiya) and exogenous (on the local societal level), by combining synchronic and diachronic approaches at the intersection of anthropology and history.This study shows that the zawiya, especially in the post-independence period, is a true center of political and social tensions. It highlights persistent ones between the involvement of local actors in the heritage of the Islam of the zawiyas, the cult of saints, and the rituals that accompany it, and their integration into the state-run spheres of official and dominant Islam. It also sheds light on the attraction-repulsion exerted by reformism and the Islamic movement. Field data show how these relations of appropriation and conflict result in a transformation of the local religious field, as well as the contradictions at work between programmatic intentions and the realities of application. These contradictions are notably evident in the project for the reorientation of religious education that the state has been pursuing for two decades. In fact, this project faces several obstacles, which explain the contradictions between the educational programs developed by the ministry (for zawiyas and Quranic schools) and the reality of teaching in these institutions. The studied case makes these contradictions and the obstacles faced by this project particularly visible. Furthermore, our knowledge of other religious institutions in Kabylia shows that while the Uqari zawiya adheres to this project, this is far from being the case in other places, where we have not found evidence of these programs. These initial results open up other research perspectives regarding the educational programs at work in the zawiyas or Quranic schools, and their relationship with the official religious bureaucracy.